OPTIMIZATION OF SLACK BUS PLACEMENT DURING PEAK LOAD BY CONSIDERING THE VOLTAGE PROFILE OF THE GENERATION BUS IN THE SULSELRABAR ELECTRICITY SYSTEM - Hamzah, Muhammad Aqmal Muslimin; Sofyan, Sofyan; Sultan, Ahmad Rizal; Bachtiar , Muhammad Imran (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2025)
This study was carried out to determine the best slack bus placement during peak loads by considering the voltage profile of the generator buses in the South Sulawesi electricity system. Analysis was performed to determine the optimal slack bus placement and its impact on the bus voltage profile. South Sulawesi's electric power system is made up of 29 power-generating units, including PLTA, PLTU, PLTG, PLTGU, PLTMH, PLTD, and PLTB, that operate at a voltage of 150 kV. In addition, 56 substations are linked via a 150 kV transmission network. This study relies on daily operational data from the South Sulawesi system at peak load on September 16, 2022. Using Matlab's Newton-Raphson method to simulate power flow, five scenarios are used to alternately change the generator bus (PV bus) into a slack bus; the generators are PLTA Bakaru, Punagaya PLTU, Jeneponto PLTU, Sengkang PLTU, and Poso PLTA. After running simulations for each generator, it was discovered that Poso PLTA had the voltage profile closest to the standard set by the Minister of Energy and Mineral Resources Regulation number 20 of 2020, which ranges between 0.90 and 1.05 pu. In comparison to the other four slack buses, it had the lowest total power loss of 120,743 MW and 593,764 MW MVAR.